Anticoagulation management services in community pharmacy: Feasibility of implementing a quality improvement programme through a practice‐based research network. (17th July 2018) - Chartrand, Mylène; Lalonde, Lyne; Cantin, Ariane; Lahaie, Alexandre; Odobasic, Bojan; Tremblay, Marie‐Philip; Wazzan, Dana; Gagnon, Marie‐Mireille; Martin, Élisabeth; Dorais, Marc; Berbiche, Djamal; Guénette, Line
Summary: What is known and objective: The literature has reported suboptimal real‐world use of oral anticoagulants in patients with atrial fibrillation (AF). Anticoagulation management services (AMSs) in community pharmacy have rarely been evaluated, and no formal process is available to enable pharmacists to evaluate and improve their clinical practices. Our objective was to assess the feasibility of implementing, through a practice‐based research network (PBRN), a quality improvement programme on AMSs by community pharmacists for AF patients and explore its impact on the quality of clinical practices and pharmacists' knowledge. Methods: An uncontrolled pre/post‐pilot study was conducted through a PBRN. Pharmacists identified 5‐20 AF patients on oral anticoagulants per pharmacy and completed questionnaires at baseline (T0) and after 6 months (T6). Clinical practices were evaluated using a set of quality indicators (QIs). QI scores ranged from 0% (no QI achieved) to 100% (all QIs achieved). The programme included an audit and feedback based on QIs and a personalized training programme (including online videos). Participation rates and satisfaction were documented. Mean changes (T6‐T0), with 95% confidence interval (CI), in QIs and knowledge scores were computed. Results and discussion: A total of 37 pharmacies (50 pharmacists) identified 222 patients who had received either vitamin K antagonists (VKAs) or direct oral anticoagulants (DOACs), or both. All pharmacies received their baseline quality report (audit), and facilitators contacted by phone 97% of pharmacies (feedback). Each of the six online videos was completed by at least 48% of pharmacists. Baseline mean global QI scores for VKAs and DOACs were 39.1% (95% CI: 35.7%‐42.4%) and 12.3% (7.8%‐16.8%), respectively. Over a 6‐month period, they increased by 12.5% points (7.5%‐17.5%) and 9.9% points (3.8%‐16.1%), respectively. Baseline mean global knowledge score was 68.7% (65.4%‐72.0%) and increased by 4.3% points (1.2%‐7.4%). What is new and conclusion: Implementing a quality improvement programme for AMS in community pharmacy is relevant and feasible and may improve pharmacists' practices and knowledge. Abstract : Anticoagulation management services (AMSs) in community pharmacy have rarely been evaluated. This study assessed the feasibility of implementing, through a practice‐based research network, a quality improvement programme on AMSs for atrial fibrillation patients. Results show the programme is relevant and feasible and may improve pharmacists' practices and knowledge.